Smart Trash Robot - Sirichai Tammaruckwattana; Ekarin Vichachuai; Apinan Seekhieo; Jirawat Patipatpong; Chonlasit Choodee; Supachai Ruangrit; Apinai Rerkratn; Narin Tammarugwattana (My University, 2026)
This paper proposes a smart trash robot system to improve the current issues in trash/waste management across various locations, including meeting rooms, buildings, and residential areas. These issues include the distance between trash bins and the incapability to monitor their working status in real-time. This often leads to overfilling waste, unpleasant odors, and diminished aesthetic appeal in public spaces. To address these challenges, we have developed the "Smart Trash Robot", designed to enhance user convenience and maintain environmental cleanliness. The robot can notify users when the bin is full via ultrasonic sensors and a mobile application. Additionally, it can autonomously move to designated locations using LiDAR sensors, which work in tandem with motorized wheels, thus reducing the need for users to travel long distances to manage waste and easy to access in all areas which route of operate can designate. The robot also features an automatic bag-sealing system, providing users with greater ease in handling trash. Furthermore, it helps maintain a clean and pleasant environment by preventing waste overflow and odors, while its touchless lid operation via infrared sensors for hygiene and safety as priority. With its integration of advanced technology, the Smart Trash Robot significantly improves waste management efficiency, reduces user workload, and fosters a cleaner, more aesthetically pleasing, and sustainable environment.
Keywords: Transportation and Mobility Innovations; Smart Parking Systems Research; Control and Dynamics of Mobile Robots